The teaching strategies and the development of students’ speaking skills in the ninth year of basic general education at Emiliano Ortega Espinoza high school in Catamayo academic period 2013-2014 - Rueda Japón, Janneth Alexandra (2015)
The present research work entitled: “THE TEACHING STRATEGIES AND THE DEVELOPMENT OF STUDENTS’ SPEAKING SKILLS IN THE NINTH YEAR OF BASIC GENERAL EDUCATION AT EMILIANO ORTEGA ESPINOZA HIGH SCHOOL IN CATAMAYO ACADEMIC PERIOD 2013-2014”had the purpose of analyzing the Teaching Strategies that the English teachers apply to promote the development of the speaking skills. The methods used to develop this research were the following: descriptive, explicative, the analytic-synthetic; Additional surveys were applied to 4 teachers and 150 students; which were used as tools to pick up the required data and then they were tabulated, organized, described in the statistical tables, graphically represented, interpreted and analyzed in its logical process which allowed obtaining conclusions and recommendations. The obtained results confirmed that teachers have knowledge about teaching strategies and they apply these strategies with their students. Therefore it was possible to verify that the use of teaching strategies influences in the development of the speaking skills